A Survey on Video-based Graphics and Video Visualization - Ben Daubney (Eurographics, 2011)
R. Borgo, M. Chen, B. Daubney, E. Grundy, H. Jänicke, Gunther Heidemann, M. Hoferlin, B. Hoferlin, D. Weiskopf, X. Xie,To appear Eurographics, 2011